Jalur Kereta Api dan Perkembangan Kota Lumajang Pada Masa Kolonial Hindia Belanda, 1893-1942 - Yuniarta, Aldilla Dinda; Pratama, Akhmad Ryan; Swastika, Kayan (Perkumpulan Program Studi Sejarah Se-Indonesia, 2024)
This research aims to examine the changes in the Afdeeling Lumajang area from a traditional city to a modern city marked by the construction of the Klakah-Pasirian railway line, which was intended as a means of transportation for goods and passengers. Historical methods are used to explain this study. The research results show that the development of the Afdeeling Lumajang area into a modern city was initially influenced by the development of railway transportation facilities for plantation purposes and passenger transportation from inland areas. The Klakah-Pasirian Railway began operating on May 16, 1896, with a train track length of 36 km using the standard rail width used in the Dutch East Indies, namely 1,067 mm. There are nine stops and stations on the Klakah-Pasirian railway line, consisting of Klakah Station, Grobogan Stop, Sukodono Stop, Lumajang Station, Labruk Stop, Tempeh Stop, Mujur Stop, Condro Stop, and Pasirian Station.